Math, asked by daksh4871, 1 year ago

the value of x in the equation 3x+4\2x +1 = x-8\2x-5​

Answers

Answered by mihir2711
3

please mark me.....

follow me

Attachments:

mihir2711: mark me
mihir2711: please
Answered by payalchatterje
0

Answer:

Required value of x is (-3) or +1.

Step-by-step explanation:

Given,3x+4\2x +1 = x-8\2x-5

 \frac{3x + 4}{2x + 1}  =  \frac{x - 8}{2x - 5}

By cross multiplication,

(3x + 4)(2x - 5) = (2x + 1)(x - 8)

We are removing brackets,

6 {x}^{2}  - 15x + 8x - 20 = 2 {x}^{2}  - 16x + x - 8

6  {x}^{2}  - 15x + 8x - 20 - 2 {x}^{2}  + 16x - x + 8 = 0

4 {x}^{2}  + 8x - 12 = 0

x =  \frac{ - 8 \pm \sqrt{ {8}^{2} +4 \times 4 \times 12 } }{2 \times 4}  \\  =  \frac{ - 8 \pm \sqrt{64 + 192} }{8}  \\  =  \frac{ - 8 \pm \sqrt{256} }{8}  \\ = (-1 \pm 2)

Therefore x = (-3) or +1

This is a problem of Algebra.

Some important Algebra formulas.

(a + b)² = a² + 2ab + b²

(a − b)² = a² − 2ab − b²

(a + b)³ = a³ + 3a²b + 3ab² + b³

(a - b)³ = a³ - 3a²b + 3ab² - b³

a³ + b³ = (a + b)³ − 3ab(a + b)

a³ - b³ = (a -b)³ + 3ab(a - b)

a² − b² = (a + b)(a − b)

a² + b² = (a + b)² − 2ab

a² + b² = (a − b)² + 2ab

a³ − b³ = (a − b)(a² + ab + b²)

a³ + b³ = (a + b)(a² − ab + b²)

Know more about Algebra,

1) https://brainly.in/question/13024124

2) https://brainly.in/question/1169549

#SPJ5

Similar questions